Perceptions of Cooperating Teachers on Pre-Service Teachers’ Mentoring in Teaching Practicum: Empirical Evidence From Initial Teacher Education - Nurhadi, Kardi; Aryani, Siska (Universitas Jambi, Magister Program of English Education Department, 2021)
Although research on cooperating teachers mentoring pre-service teachers provide important findings in teacher education, a few of studies on exploring cooperating teacher’s perception on pre-service teachers mentoring situated in Indonesian teacher education. Grounded in narrative inquiry design, this research report how cooperating teachers perception on mentoring their pre service teachers in teaching practicum. Two cooperating teachers agree to participate in this study voluntarily. Data were derived from semi structured interview which focus on exploring the critical incidents while they were mentoring pre service teachers. The data were qualitatively using thematic analysis by Braun & Clarke (2006). Findings revealed that pre-service teachers’ difficulties in using English to teach the students, pre-service teacher were given beneficial in teaching by applying strategies and media. While, for mentoring aspects, pre-service teachers were lack of prepared of lesson plan and the pre-service teachers communication during teaching practicum were good. In understanding teaching material, pre-service teachers need to engage their ability. The pre-service teachers were still weak in reviewing the material and giving assignment. They cannot manage the class and time well so there is not enough time to review the material.